2023
DOI: 10.3390/nu15061477
|View full text |Cite
|
Sign up to set email alerts
|

Diet as a Factor Supporting Lung Cancer Treatment—A Systematic Review

Abstract: The purpose of this study was to summarize the evidence from epidemiological studies concerning associations between diet and the effectiveness of treatment for lung cancer. For this review, a literature search has been conducted in the EMBASE and PubMed databases, including papers published between 1977 and June 2022. The term “lung cancer” was used in conjunction with “diet”. Footnotes from the selected papers were also analyzed. The present study is in line with the recommendations included in the Preferred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Our results are another clear and relevant example that may demonstrate, at least in part, the adverse effects and conflicting results in lung studies in patients with vitamin A supplementation. In this context, several references have shown that vitamin A intake enhances TNF-α and is also associated with oxidative stress and increased proinflammatory cytokines in lung tissue; thus, a retinoid overdose may have a negative impact on maintaining tissue integrity [ 50 , 51 , 52 , 53 , 54 ]. In addition, there are conflicting results that correlate vitamin A with increased carcinogenic risk [ 55 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results are another clear and relevant example that may demonstrate, at least in part, the adverse effects and conflicting results in lung studies in patients with vitamin A supplementation. In this context, several references have shown that vitamin A intake enhances TNF-α and is also associated with oxidative stress and increased proinflammatory cytokines in lung tissue; thus, a retinoid overdose may have a negative impact on maintaining tissue integrity [ 50 , 51 , 52 , 53 , 54 ]. In addition, there are conflicting results that correlate vitamin A with increased carcinogenic risk [ 55 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer is a disease with high morbidity and mortality worldwide (second only to breast cancer in incidence), with a 5-year survival rate of only 24%; ( 1 , 2 ). Although various methods such as surgery, chemotherapy, and radiotherapy are used to treat NSCLC and SCLC, the main treatment for lung cancer patients is chemotherapy ( 3 , 4 ). Chemoprevention refers to the use of drugs or natural substances to delay or reverse the carcinogenic process and is one of several promising strategies to reduce cancer development ( 5 ).…”
Section: Popular Scientific Summarymentioning
confidence: 99%
“…Lung cancer is the most common malignancy in the world, and has a high lethality; therefore, it generates a great burden for healthcare systems in the world [1]. Pola ński et al reviewed the role of a diet as a supportive factor in lung cancer treatment and reported some interesting findings [2]. The authors point out that polyunsaturated fatty acids (PUFAs), particularly ω-3 PUFA, which includes eicosapentaenoic acid (EPA), may lessen inflammation, reduce muscle loss, and alter important pathways that drive the development of lung cancer [3,4].…”
mentioning
confidence: 99%
“…According to the review authors, the goal of any planned intervention should be to prevent malnutrition. Future research is challenged by the paucity of data on effective diet-related preventive strategies for lung cancer, which hinders the ability to draw valid conclusions [2].…”
mentioning
confidence: 99%